Peran Budaya Di Prodi Komunikasi Universitas Sari Mutiara - Nurhawati Simamora; Evi Enitari Napitupulu; Mega Ulva Sari Sihombing; Forianto Laia (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
The rapid development of Science and Technology, especially in the field of communication, has facilitated population mobility and communication that encourages an increase in the intensity of direct and indirect cultural contacts. This is clearly seen from the diverse origins and cultures of students in Malang City, especially at Tribhuwana Tunggadewi University, Malang. Of course, this is a challenge for students with diverse cultures that allow discrimination to occur, but it is actually a positive thing that plays a role in overcoming miscommunication between students. This study uses a qualitative descriptive research method with documentation data collection. Respondents were taken using sampling techniques (purposive sampling and snowball sampling). To measure the validity of the validity of the data in this study, an examination was carried out using the degree of trust technique, namely feer debriefing and triangulation. Furthermore, data analysis uses the interactive data analysis model of the Miles and Huberman model (1992) which includes data reduction as well as drawing conclusions and verification. This study can ultimately reveal several things as follows: The process of intercultural communication between students of the Communication Science Study Program is still regional. The role of intercultural communication is quite large in overcoming miscommunication between students.